INVESTIGATING THE VOCABULARY SIZE OF THE SIXTH SEMESTER STUDENTS OF INTERNATIONAL RELATIONS OF SOCIAL AND POLITICAL SCIENCE FACULTY AT UNIVERSITY OF RIAU - Lestari, Endang; Masyhur, Masyhur; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is a descriptive-quantitative research design which is aimed at investigating the vocabulary size of International Relations students of Social and Political Science Faculty at University of Riau. The subjects of this study were the sixth-semester students majoring in International Relations of Social and Political Science Faculty at University of Riau. 96 students employed in this study were given the Vocabulary Size Test created by Nation I. S. P. and Beglar D. in 2007. The findings of this study revealed that the student knew about 7,400 word families. This result showed that the participants had good vocabulary mastery. Based on Nation (2006) the mean score of students of International Relations of Social and Political Science Faculty at University of Riau in sixth semester were able to read authentic materials which contains many vocabularies.Key Words: Vocabulary, Vocabulary Size Test, International Relations